Autologous G-CSF-Mobilized Peripheral Blood CD34+ Cell Therapy for Diabetic Patients with Chronic Nonhealing Ulcer. Issue 2 (March 2014) - Tanaka, Rica; Masuda, Haruchika; Kato, Shunichi; Imagawa, Kotaro; Kanabuchi, Kazuo; Nakashioya, Chie; Yoshiba, Fumiaki; Fukui, Tsuyoshi; Ito, Rie; Kobori, Michiru; Wada, Mika; Asahara, Takayuki; et al.
Recently, animal studies have demonstrated the efficacy of endothelial progenitor cell (EPC) therapy for diabetic wound healing. Based on these preclinical studies, we performed a prospective clinical trial phase I/IIa study of autologous G-CSF-mobilized peripheral blood (PB) CD34 + cell transplantation for nonhealing diabetic foot patients. Diabetic patients with nonhealing foot ulcers were treated with 2 × 10 7 cells of G-CSF-mobilized PB CD34 + cells as EPC-enriched population. Safety and efficacy (wound closure and vascular perfusion) were evaluated 12 weeks posttherapy and further followed for complete wound closure and recurrence. A total of five patients were enrolled. Although minor amputation and recurrence were seen in three out of five patients, no death, other serious adverse events, or major amputation was seen following transplantation. Complete wound closure was observed at an average of 18 weeks with increased vascular perfusion in all patients. The outcomes of this prospective clinical study indicate the safety and feasibility of CD34 + cell therapy in patients with diabetic nonhealing wounds.